1991
DOI: 10.1177/019262339101900404
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Cardiomyopathy and Hemothorax in Vitamin K Deficient Mice

Abstract: The cause of a fatal condition characterized by hemorrhagic cardiomyopathy, hemothorax, and coagulation defects in hysterectomy-derived male mice was investigated. Microscopic heart alterations included multifocal hemorrhage and necrosis with variable degrees of acute inflammation and fibroplasia that were most severe in the region of the atrioventricular junction. A spontaneous outbreak was arrested by increasing menadione Na-bisulfite (vitamin K) in the feed to 20 ppm. The complete syndrome including hemorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In previous studies, multifocal hemorrhage and necrosis with varying degrees of acute inflammation and fibrosis have been reported in vitamin K-deficient mice [1,5,9,11]. Coagulation defects, including prolonged PT, have also been reported [5,11].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In previous studies, multifocal hemorrhage and necrosis with varying degrees of acute inflammation and fibrosis have been reported in vitamin K-deficient mice [1,5,9,11]. Coagulation defects, including prolonged PT, have also been reported [5,11].…”
Section: Discussionmentioning
confidence: 95%
“…A variety of factors other than vitamin K deficiency secondary to altered intestinal microflora of this disease have been suspected of causing or contributing to the outbreaks [5], including infectious agents [4], ethylene glycol contamination of cage bedding [11] and increased dietary lipoperoxides complicated by vitamin K and/or E deficiency [9]; however, the factor(s) responsible for the disease were not fully identified in these reports. Allen et al [1] first described the mortality of mice attributable to hemorrhagic diathesis in NIH Genetic Resource colonies in 1971. They concluded that the cause of hemorrhagic cardiomyopathy and hemothorax was vitamin K deficiency based on controlled studies using germfree mice given a vitamin K-free diet and conventional mice given warfarin in their diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fritz et al (1968) described varying degrees of hepatic degeneration and hepatomegaly in addition to cardiac lesions and hemorrhages in rodents, which died of coagulopathy related to vitamin K deficiency. These findings suggest that the focal/multifocal hepatocellular necrosis (often with hemorrhage) in the dietary studies was also produced by an effect on vitamin K. The higher susceptibility of males for developing hemorrhagic cardiomyopathy related to vitamin K deficiency has also been described by Allen et al (1991) and Fritz et al (1968). The protecting role of estrogen against vitamin K deficiency has been described in several articles, and Mellette (1961) demonstrated that the onset of vitamin K deficiency in rats was enhanced in the spayed female and retarded in the castrated male.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, the term hemorrhagic cardiomyopathy (with hemothorax) was adopted, and it was decided to further explore if the compound could have an effect on vitamin K, and via this mechanism, cause changes similar to those described by Allen et al (1991) and Fritz et al (1968). Indeed, in a 3-month dietary rat study with the compound, prolongation of prothrombin time (PT) and activated partial thromboplastin time (APTT) had been noticed in males but were not noted in female rats or the dog.…”
mentioning
confidence: 99%